From Java to C♯ : a developer's guide - Mok, Heng Ngee (Addison-Wesley, 2003)
The fastest way for Java developers to pick up C# and .Net - by leveraging on what they already know in Java to learn the new language. Allows a Java developer to pick up C# as quickly as possible by highlighting the similarities and differences between the two languages. Extensive detailed coverage of the new features in C# not found in Java. A useful introduction to the .NET platform and how the new architecture works. It's important for a C# developer to know what happens behind the scenes. User Level: Intermediate. Audience: All intermediate Java developers. Technology: C# is a new programming language which is promoted by Microsoft as the successor to C++. C# together with Visual Basic .NET are the two most popular programming languages .NET developers use to write applications targeted at the .NET platform. Author Biography: Mok Heng Ngee is an experienced software developer and architect who has been involved in numerous large-scale software enterprise projects based on the Java 2 Platform, Enterprise Edition (J2EE). Mok has writes for Computer Times and has been invited to speak at the official launch of Visual Studio .NET in Singapore. He has been accorded MVP (Most Valuable Professional) status by Microsoft Asia.